Multi-organ spreading of Actinobacillus pleuropneumoniae serovar 7 in weaned pigs during the first week after experimental infection - Hoeltig, Doris (Vet Res, 2018)
Actinobacillus (A.) pleuropneumoniae is normally considered strictly adapted to the respiratory tract of swine. Despite this, scattered case reports of arthritis, osteomyelitis, hepatitis, meningitis or nephritis exist, in which A. pleuropneumoniae remained the only detectable pathogen. Therefore, the aim of this study was to investigate whether spreading to other organs than the lungs is incidental or may occur more frequently. For this, organ samples (blood, liver, spleen, kidney, tarsal and carpal joints, meninges, pleural and pericardial fluids) from weaners (n = 47) infected experimentally with A. pleuropneumoniae serovar 7 by aerosol infection (infection dose: 10.9 × 10(3) cfu/animal) were examined by culture during the first week after infection. In addition, tissue samples of eight weaners were examined by histology and immunohistochemistry (IHC). A. pleuropneumoniae was isolated in all examined sample sites (86.7% pleural fluids, 73.3% pericardial fluids, 50.0% blood, 61.7% liver, 51.1% spleen, 55.3% kidney, 14.9% tarsal joints, 12.8% carpal joints, 27.7% meninges). These results were also obtained from animals with only mild clinical symptoms. IHC detection confirmed these findings in all locations except carpal joints. Histological examination revealed purulent hepatitis (n = 2), nephritis (n = 1) and beginning meningitis (n = 2). Isolation results were significantly correlated (p < 0.001) with the degree of lung colonization and, to a lower extent, with the severity of disease. Detection of A. pleuropneumoniae in peripheral tissues was significantly correlated to spleen colonization. In conclusion, multi-organ spreading of A. pleuropneumoniae serovar 7 strain AP 76 seems to occur more frequently during acute infection following effective lung colonization than previously thought.